Energy pumping in a quantum nanoelectromechanical system - Nord, T.; Gorelik, L.Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Fully quantized mechanical motion of a single-level quantum coupled to two voltage biased electronic leads is studied. It is found that there are two different regimes depending on the applied voltage. If the bias voltage is below a certain threshold (which depends on the energy of the vibrational quanta) the mechanical subsystem is characterized by a low level of excitation. Above a threshold the energy accumulated in the mechanical degree of freedom dramatically increases. The distribution function for the energy level population and the current through the system in this regime is calculated.